The Development and Evaluation of PFSA-Free Polyacrylonitrile-co-Methyl Acrylate (PAN-MA) Nanofiber Membranes for its Potential Application as a Proton Exchange Membrane in Fuel Cells - Seda, Koeksal Yegin; Oner, Mualla; Remis, Tomas; Tomas, Martin; Kovarik, Tomas (WILEY-V C H VERLAG GMBH, 2024)
The significance of hydrogen energy has grown considerably due to climate change and the depletion of fossil fuels. PEM fuel cells are the key hydrogen technologies. Commercial membranes based on perfluorosulfonic acid (PFSA) with a polymer structure containing fluorine are currently available. However, it has been determined that certain perfluorosulfonic acids (PFSAs) are hazardous, persistent, and bioaccumulative. Advancements in hydrogen technology rely on effective, inexpensive, and perfluorocarbon-free membranes, specifically proton exchange membranes (PEMs). In this research, a PFSA-free polyacrylonitrile-co-methyl acrylate (PAN-MA) membrane doped with phosphoric acid is prepared using the electrospinning method and then characterized by SEM, FE-SEM, XRD, FTIR, TGA, DMA, and EIS. The DMA analysis reveals that the storage modulus of the doped membrane increases from 0.98 to 5.66 MPa at 80 degrees C. The nanofiber composite membrane, with a thickness of 181 mu m, exhibits the highest proton conductivity of 0.306 S m(-1) at 20 degrees C, 1.76 times higher than that of the Nafion 212 membrane. The Nafion 212 membrane has an ionic conductivity of 0.173 S m(-1) under the same conditions. These results indicate that the prepared nanofiber membranes are promising materials for evaluating fuel cell applications.
Keywords: fuel cells; membranes; nanofibers; polyacrylonitrile copolymers; Materials Science; Polymer Science